Acid leaching of hydrothermally carbonized sewage sludge: phosphorus recovery and hydrochar characteristics - Shettigondahalli Ekanthalu, Vicky; Ender, Tommy; Narra, Satyanarayana; Antwi, Edward; Bej, Saptarshi; Nelles, Michael (Frontiers in Environmental Engineering, 2023)
The option for managing sewage sludge and its utilization as fertilizer is becoming progressively limited as a result of stringent environmental regulations imposed by the European Union over the past ten years. In comparison to the conventional sewage sludge treatment options like incineration, the limitation of moisture present in sewage sludge can be obviated by using the hydrothermal carbonization (HTC) process. This research investigates the acid leaching of hydrochar produced by hydrothermally carbonizing sewage sludge. The objective is to investigate and compare the effects of formic acid (HCOOH), sulfuric acid (H2SO4) and acetic acid (CH3COOH) at varying pH levels on total phosphorus (TP) mobilization and hydrochar properties. The impact of independent parameters such as carbonization temperature of hydrochar, acid type, acid concentration, acid leaching retention time on the TP mobilization, chemical oxygen demand (COD) of the leachate, and the fuel characteristic of the hydrochar was explored. A quadratic and cubic model was proposed to correlate the effects of independent parameters on TP and ortho-P mobilization, acid need, COD of leachate, and fuel characteristics of hydrochar using Design of experiment and Response Surface Modeling. This approach was chosen in order to maximize the amount of data from a constrained number of experimental trials. The outcome of the study indicated a fractional amount of H2SO4 was enough to reach and maintain the lower pH in hydrochar slurry in comparison with HCOOH and CH3COOH. TP mobilization from solid to liquid is highly favorable in the presence of H2SO4 lower pH in comparison with HCOOH and CH3COOH at similar reaction conditions. In addition, it was This is a provisional file, not the final typeset article discovered that lowering the pH using HCOOH and H2SO4 to acid-leach the hydrochar boosted the calorific value of the hydrochar. CH3COOH however has a contradicting effect.